ETNOMATEMATIKA PADA KERAJINAN ANYAMAN PANDAN DI DESA GRENGGENG KEBUMEN SEBAGAI MEDIA PEMBELAJARAN MATEMATIKA - Mubarok, Mohamad Sukkron (IAIN Pontianak, 2025)
This research is based on the assumption that mathematics is a difficult to understand and boring science, resulting in low attraction and interest of students when meeting mathematics subjects. Therefore, it is necessary to have learning support tools so that it is easier to deliver material so that students do not experience difficulties. The research focuses on analyzing mathematical concepts in pandan weaving crafts and exploring information related to the initial response if pandan weaving crafts are used as a mathematics learning medium. This study uses a qualitative descriptive research type with an ethnographic approach. Data obtained from the results of documentation and interviews. The data analysis techniques used are domain analysis, taxonomic analysis, component analysis and cultural theme analysis. In domain analysis, it consists of the domain of objects, tools and images. In taxonomic analysis, it is in the form of a concept map. In the component analysis, it is in the form of re-checking each component to obtain the validity of the data. In the analysis of cultural themes, five sub-themes were found in the form of geometry, lines, angles, congruence and revival. The results of the study showed an analysis of the existence of mathematical concepts contained in pandan weaving crafts. The results of the discussion showed that information related to pandan weaving crafts was used as a mathematics learning medium that received a fairly good initial response from mathematics teachers because it could make it easier to convey material, hone thinking skills and make it possible to make students attractive and interested in learning mathematics.